Streamlining of Medical Relief to Areas Affected by the Great East Japan Earthquake with the "Area-based/Line-linking Support System". Issue 6 (22nd October 2014) - Yamanouchi, Satoshi; Ishii, Tadashi; Morino, Kazuma; Furukawa, Hajime; Hozawa, Atsushi; Ochi, Sae; Kushimoto, Shigeki
Abstract Introduction When disasters that affect a wide area occur, external medical relief teams play a critical role in the affected areas by helping to alleviate the burden caused by surging numbers of individuals requiring health care. Despite this, no system has been established for managing deployed medical relief teams during the subacute phase following a disaster. After the Great East Japan Earthquake and tsunami, the Ishinomaki Medical Zone was the most severely-affected area. Approximately 6, 000 people died or were missing, and the immediate evacuation of approximately 120, 000 people to roughly 320 shelters was required. As many as 59 medical teams came to participate in relief activities. Daily coordination of activities and deployment locations became a significant burden to headquarters. The Area-based/Line-linking Support System (Area-Line System) was thus devised to resolve these issues for medical relief and coordinating activities. Methods A retrospective analysis was performed to examine the effectiveness of the medical relief provided to evacuees using the Area-Line System with regards to the activities of the medical relief teams and the coordinating headquarters. The following were compared before and after establishment of the Area-Line System: (1) time required at the coordinating headquarters to collect and tabulate medical records from shelters visited; (2) time required at headquarters to determine deployment locations and activities of all medical relief teams; and (3) inter-area variation in number of patients per team. Results The time required to collect and tabulate medical records was reduced from approximately 300 to 70 minutes/day. The number of teams at headquarters required to sort through data was reduced from 60 to 14. The time required to determine deployment locations and activities of the medical relief teams was reduced from approximately 150 hours/month to approximately 40 hours/month. Immediately prior to establishment of the Area-Line System, the variation of the number of patients per team was highest. Variation among regions did not increase after establishment of the system. Conclusion This descriptive analysis indicated that implementation of the Area-Line System, a systematic approach for long-term disaster medical relief across a wide area, can increase the efficiency of relief provision to disaster-stricken areas. <mixed-citation id="ref" publication-type="journal"> <string-name> <given-names>S</given-names> <x content-type="archive" xml:space="preserve"> </x> <surname>Yamanouchi</surname> </string-name>, <string-name><given-names>T</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Ishii</surname></string-name>, <string-name><given-names>K</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Morino</surname></string-name>, <string-name><given-names>H</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Furukawa</surname></string-name>, <string-name><given-names>A</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Hozawa</surname></string-name>, <string-name><given-names>S</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Ochi</surname></string-name>, <string-name><given-names>S</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Kushimoto</surname></string-name>. Streamlining of medical relief to areas affected by the Great East Japan Earthquake with the "Area-based/Line-linking Support System." <source>Prehosp Disaster Med</source>. <year>2014</year>;<volume>29</volume>(<issue>6</issue>):<fpage>1</fpage>-<lpage>9</lpage></mixed-citation>.